HUMAN RIGHTS CONCEPTUALITY IN ISLAMIC AND WESTERN REALITY TERMINOLOGY - Alfian Alfian; Teuku Muzaffarsyah (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2023)
Human rights are generally understood as rights that absolutely become basic rights where people inherently have rights because of their position as human beings which include aspects of nation, location, language, religion, ethnicity, and other statuses. There is a principled difference between human rights seen from an Islamic and western point of view. In fact, the root of the problem between Islamic and Western civilizations is not from the Islamic religion or not, but because of the different structural foundations that are used as a basis for both. Islam is against the social class system in any form. Meanwhile, the West always claims that the concept of human rights originates from their civilization. On the other hand, the Islamic world also claims that this concept originates from the original teachings of Islam. In applying the principle of justification, a paradigm shift is required from the exclusionist interpretation of international human rights law. However the authors mention that the points of similarity are far more general than the differences. Points of difference do not have to be avoided, but reconstructed in order to find common ground. In this way, Islam is compatible with the dynamics and developments of the times.Hak Asasi Manusia secara umum dipahami sebagai hak yang mutlak menjadi hak dasar dimana manusia secara inheren memiliki hak karena kedudukannya sebagai manusia yang meliputi aspek bangsa, tempat, bahasa, agama, suku, dan status lainnya. Ada perbedaan prinsip antara hak asasi manusia dilihat dari sudut pandang Islam dan Barat. Padahal, akar permasalahan antara peradaban Islam dan Barat bukanlah dari agama Islam atau bukan, melainkan karena perbedaan landasan struktural yang dijadikan landasan keduanya. Islam menentang sistem kelas sosial dalam bentuk apapun. Sedangkan Barat selalu mengklaim bahwa konsep hak asasi manusia berasal dari peradaban mereka. Di sisi lain, dunia Islam juga mengklaim bahwa konsep ini bersumber dari ajaran Islam yang asli. Dalam menerapkan asas pembenaran, diperlukan pergeseran paradigma dari penafsiran yang ekslusif terhadap hukum HAM internasional. Namun penulis menyebutkan bahwa poin kesamaan jauh lebih umum daripada perbedaannya. Titik perbedaan tidak harus dihindari, tetapi direkonstruksi untuk menemukan titik temu. Dengan demikian, Islam sesuai dengan dinamika dan perkembangan zaman.